The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1152/ajpgi.00226.2021
|View full text |Cite
|
Sign up to set email alerts
|

Yeast β-glucan reduces obesity-associated Bilophila abundance and modulates bile acid metabolism in healthy and high-fat diet mouse models

Abstract: Emerging evidence links dietary fiber with altered gut microbiota composition and bile acid signaling in maintaining metabolic health. Yeast β-glucan (Y-BG) is a dietary supplement known for its immunomodulatory effect, yet its impact on the gut microbiota and bile acid composition remains unclear. This study investigated whether dietary forms of Y-BG modulate these gut-derived signals. We performed 4-week dietary supplementation in healthy mice to evaluate effects of different fiber composition (soluble vs pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Bilophila, belongs to phylum Desulfobacterota, is a kind of bile-tolerant microorganisms, which is associated with the development of obesity. [48,49] Nativida et al [50] found that HFD is beneficial to the growth of the Bilophila wadsworthia, and the synergy of the HFD and B. wadsworthia promoted inflammation, bile acid metabolism disorders, and intestinal barrier dysfunction, resulting in the glucose metabolism disorder and liver steatosis. Our study pointed out that EU supplementation reduced the relative abundance of Bilophila in mice fed with HFD.…”
Section: Discussionmentioning
confidence: 99%
“…Bilophila, belongs to phylum Desulfobacterota, is a kind of bile-tolerant microorganisms, which is associated with the development of obesity. [48,49] Nativida et al [50] found that HFD is beneficial to the growth of the Bilophila wadsworthia, and the synergy of the HFD and B. wadsworthia promoted inflammation, bile acid metabolism disorders, and intestinal barrier dysfunction, resulting in the glucose metabolism disorder and liver steatosis. Our study pointed out that EU supplementation reduced the relative abundance of Bilophila in mice fed with HFD.…”
Section: Discussionmentioning
confidence: 99%
“…Bilophila was associated with obesity in mice induced by a high-fat diet ( 41 ), but it was also found to be significantly negatively correlated with broiler weight ( 42 ). As a potential beneficial bacterium, Akkermansia was more abundant in the better-fed efficacy group hens ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, gallbladder bacteria are closely related to the formation of obesity, and Fermentum β-polysaccharide could significantly reduce the abundance of gallbladder bacteria. In addition to reducing obesity-related gallbladder bacteria, Fermentum β-polysaccharide also increased the abundance of liver Cyp7a1 mRNA and bile acid synthesis, effectively alleviating obesity-related diseases in obese mice ( So et al, 2021 ). According to another study, Fermentum β-polysaccharide significantly inhibited the high expression of SGLT-1, a major glucose transporter protein in the small intestinal mucosa.…”
Section: Activitymentioning
confidence: 99%